Shakin' All Over: Die Beatmusik in der Bundesrepublik Deutschland 1963-1967 - Klitsch, Hans-Jürgen (Germany High Castle, 2000)
Hans-Jürgen Klitsch 'Shakin' All Over' is not only a socio-cultural history of the sixties, but also the family album of a generation out of control. The book that put the Bundesrepublik Deutschland on the international map as a beat nation.
Keywords: 20th Century (1901-2000); Music history; Cultural history; Sociology; Popular music; Germany